Discrepancies between crystallized and fluid ability are associated with frequency of social and physical engagement in community dwelling older adults. Issue 10 (26th November 2018) - O'Shea, Deirdre M.; Fieo, Robert; Woods, Adam; Williamson, John; Porges, Eric; Cohen, Ron
ABSTRACT: Objective : Age differences have been noted in the discrepancies between crystallized and fluid ability (G c –G f ). Larger G c –G f discrepancies have also been shown to be associated with Alzheimer's disease biomarkers and clinical severity. However, little is known regarding the relationship between G c –G f discrepancies in normal aging and functional outcomes. The aim of the present study was to examine this. Method : Data from 104 adults ( M age  = 71.70 years, SD  = 9.016) were included in the present study. Measures from the NIH toolbox were used to form the discrepancy scores. Physical, cognitive, and social activities were identified using the Community Healthy Activities Model Program for Seniors activity questionnaire. Linear regression analyses, controlling for age, education, gender, health, and depressive symptoms, were used to examine the association between social, cognitive, and physical activities on G c –G f discrepancies. Results : Results showed that social and physical activity were significantly associated with greater discrepancies between crystallized and fluid ability, independent of covariates. There was no association between cognitive activity and G c –G f discrepancies. Conclusions : Larger discrepancies between crystallized and fluid ability are related to frequency of social and physical activity. The findings support previous research that discrepancy scores may serve as a marker of cognitive decline. In more highly educated older individuals, G c –G f discrepancies may be a more accurate indicator of actual cognitive status.